ChemInform Abstract: Intermolecular Visible‐Light Photoredox Atom‐Transfer Radical [3 + 2]‐Cyclization of 2‐(Iodomethyl)cyclopropane‐1, 1‐dicarboxylate with Alkenes and Alkynes. Issue 3 (21st January 2014) - Gu, Xiangyong; Li, Xiang; Qu, Yue; Yang, Qi; Li, Pixu; Yao, Yingming
Abstract Less reactive alkenes or alkynes require the addition of zinc acetate as promotor.